Oral Health-Related Quality-of-Life According to Dental Caries Severity, Body Mass Index and Sociodemographic Indicators in Children with Special Health Care Needs - Rawan Rasheed Alwattban (MDPI AG, 2021)
This study aimed to assess the impact of dental caries’ severity, body mass index (BMI), and sociodemographic factors on oral health-related quality of life (OHRQoL) for special health care needs (SHCN) children and the suitability of their caregivers as proxies to determine OHRQoL. This cross-sectional study recruited 107 pairs of SHCN children and their caregivers and asked them to complete a questionnaire on sociodemographic issues as well as the Arabic version of the early childhood oral health impact scale (A-ECOHIS). This was followed by a dental examination. Dental caries was measured using the dmft/DMFT index, while caries’ severity was also determined. The children’s height and weight were measured, and BMI (kg/m2) was recorded. Data were analyzed statistically using t-test, one-way ANOVA, and Poisson regression models. Our results revealed that the A-ECOHIS score was 10.93, while the OHRQoL was affected in 95.3% of children. The most-reported item was ‘pain in the teeth, mouth, or jaws’ (48.7%). By regression analysis, caries-free children (Odds Ratio (OR): 0.650) or those who had moderate caries (OR: 0.551) were less likely to have a negative impact on their OHRQoL than those with severe caries. Additionally, those whose caregivers had a maximum primary education (OR: 0.656) or whose occupation was in the health sector (OR: 0.721) were less likely to have a negative impact on their OHRQoL. Those who were ≤ 6 years old (OR: 1.188) were more likely to have a negative impact. BMI did not have a significant impact on the OHRQoL of the children. Further, we detected a significant positive correlation between children’s dmft/DMFT scores and the A-ECOHIS scores reported by the mothers. Given these variables, which included dental caries’ severity, but not BMI, and caregivers’ education level and occupation, plus the child’s age group, we found a significant impact on the OHRQoL. However, we found that mothers were better proxies for their children’s OHRQoL.